GOVERNING THE COMMONS: AN ANALYSIS OF TRANSBOUNDARY HAZE POLLUTION GOVERNANCE AND DIPLOMATIC TENSIONS IN SOUTHEAST ASIA - Novák, Martin; Ková?ová, Katarína; Michalík, Jozef (Yayasan Adra Karima Hubbi, 2025)
The persistent issue of transboundary haze pollution in Southeast Asia, primarily caused by forest fires, has led to significant environmental, economic, and health challenges. The complexities of managing this issue are compounded by the diplomatic tensions between affected countries, particularly Indonesia, Malaysia, Singapore, and Thailand. This study explores the governance mechanisms in place to address transboundary haze pollution and analyzes the diplomatic conflicts that arise in attempts to mitigate this shared environmental problem. By examining the role of regional cooperation, international agreements, and domestic policies, the study aims to evaluate the effectiveness of current governance structures in tackling haze pollution. This research employs a qualitative methodology, utilizing document analysis of ASEAN agreements, government policies, and academic literature, alongside expert interviews to assess the effectiveness of regional governance frameworks such as the ASEAN Haze Action Plan. The findings suggest that while regional cooperation has improved, significant diplomatic tensions persist, particularly related to the enforcement of regulations and responsibilities for pollution control. The study concludes that stronger enforcement mechanisms, enhanced regional cooperation, and the involvement of non-state actors are necessary for more effective governance of transboundary haze pollution. The research contributes to the broader discussion on environmental diplomacy and the challenges of governing global commons in Southeast Asia.